Disiplin Pegawai Kitchen di Nichi Izakaya Bandung - Heri Sutardi; Bryan Ericko (SENTRI: Jurnal Riset Ilmiah, 2026)
This study investigates the effects of servant leadership and spiritual service quality on organizational engagement through the mediating role of sense of belonging in faith-based communities. Employing an explanatory quantitative design, data were collected from 215 active members of a parish-level faith community through purposive sampling using a five-point Likert scale questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via WarpPLS 7.0. Results reveal that spiritual service quality significantly predicts both sense of belonging (β = 0.689, p < 0.001) and organizational engagement (β = 0.145, p = 0.015), while sense of belonging is a strong predictor of organizational engagement (β = 0.649, p < 0.001). Sense of belonging fully mediates the pathway from spiritual service quality to organizational engagement (β_indirect = 0.447, p < 0.001), but does not mediate the servant leadership pathway significantly. Servant leadership shows no direct or significant indirect influence on engagement. The model demonstrates substantial explanatory power (R² = 0.599; GoF = 0.595). The findings underscore that in value-based organizations, spiritual experience quality and psychological belonging are more decisive drivers of engagement than formal leadership structures. Implications for organizational management theory and practice in faith-based settings are discussed.